Disentangling the influence of reservoir abundance and pathogen shedding on zoonotic spillover of the Leptospira agent in urban informal settlements - Soni, Nirali; Eyre, Max T.; Souza, Fábio N.; Diggle, Peter J.; Ko, Albert I.; Begon, Mike; Pickup, Roger; Childs, James E.; Khalil, Hussein; Carvalho-Pereira, Ticiana S. A.; Pertile, Arsinoê C.; Carvalho, Mayara; et al. (Frontiers in Public Health, 2024)
Rats are major reservoirs for pathogenic Leptospira, the bacteria causing leptospirosis, particularly in urban informal settlements. However, how variation in rat abundance and pathogen shedding rates affects spillover transmission to humans remains unclear. This study aimed to investigate how spatial variation in reservoir abundance and pathogen pressure affect Leptospira spillover transmission to humans in a Brazilian urban informal settlement. A longitudinal eco-epidemiological study was conducted from 2013 to 2014 to characterise the spatial distribution of rat abundance and Leptospira shedding rates in rats and determine the association with human infection risk in a cohort of 2,206 community residents. Tracking plates and live-trapping were used to measure rat abundance and quantify rat shedding status and load. In parallel, four sequential biannual serosurveys were used to identify human Leptospira infections. To evaluate the role of shedding on human risk, we built three statistical models for: 1) the relative abundance of rats, 2) the shedding rate by individual rats, and 3) human Leptospira infection, in which ‘total shedding’, obtained by multiplying the predictions from those two models, was used as a risk factor. We found that Leptospira shedding was associated with older and sexually mature rats and varied spatially and temporally — higher at valley bottoms and with seasonal rainfall (December to March). The point estimate for ‘total shedding’ by rat populations was positive, i.e., Leptospira infection risk increased with total shedding, but the association was not significant (odds ratio [OR]=1.1; 95% confidence interval [CI]: 0.9, 1.4). This positive trend was mainly driven by rat abundance, rather than individual rat shedding (OR=1.8; 95% CI:0.6, 5.4 vs. OR=1.0; 95% CI:0.7, 1.4). Infection risk was higher in areas with more vegetative land cover (OR=2.4; 95% CI: 1.2, 4.8), and when floodwater entered the house (OR=2.4; 95% CI: 1.6, 3.4). Our findings indicate that environmental and hydrological factors play a more significant role in Leptospira spillover than rat associated factors. Furthermore, we developed a novel approach combining several models to elucidate complex links between animal reservoir abundance, pathogen shedding and environmental factors on zoonotic spillover in humans that can be extended to other environmentally transmitted diseases.